Violence in Early Childhood: A Systematic Literature Review - Sukma, Aflaha Tazkiyati; Rohmah, Naili (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study examines the violence that is often experienced by children in early childhood, aiming to identify the forms of violence that are often experienced by children aged 5-6 years. The method used is Systematic Literature Review with literature obtained from Google Scholar using the help of Publish or Perish. Ten articles being obtained and being review. The results of the study show that physical violence and verbal violence are forms of violence that are often experienced by early childhood, especially at the age of 5-6 years. This violence is often carried out by parents, especially with authoritarian parenting. The impact of violence experienced by children can affect children's growth and development.